Effects of a 16-week strength-training program on soccer players - Ruivo, R. M.; Carita, A. I.; Pezarat-Correia, P. (Science & Sports, 2016)
Aim: The purpose of this study was to evaluate the effects of a 16-week strength-training program applied to Chinese soccer players 15-19 years old. Methods: Twenty-eight Chinese adolescent male soccer players (16.2 years ± 1.1) from Wsports Seven Team took part in this study. During 16 weeks after one-hour football training, the players took part in a supervised strength-training program. This strength-training protocol was administered three times a week, lasted 40 min approximately and in each session they split the muscles trained. On Tuesdays, they would train chest and biceps, legs and shoulder on Wednesday and back and triceps on Friday. In the beginning and after the 16-week intervention, we evaluated body composition, resting heart rate and blood pressure, maximal oxygen uptake, upper body resistance and one maximum repetition in the bench press and lat machine. Results: Significant differences were observed in upper body endurance and strength from pre-test to post-test with an increase in push-up repetitions (43.7 ± 13.8 vs 54.1 ± 12.7) and one maximum repetition in the bench press (57.2 ± 14.5 vs 74.8 ± 15.1). In what concerns maximal oxygen uptake, a significant improvement during the intervention period was also observed (53.3 ± 2.4 vs 54.7 ± 3.3). Conclusion: The 16-week strength-training program applied in Chinese soccer players (15-19 years old) was successful in improving muscular endurance and maximal strength together with a better body composition. This study supports the introduction of strength training in the yearly soccer player planning.